2011
DOI: 10.1001/dmp.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Workers' Ability and Willingness to Report to Work During Public Health Emergencies

Abstract: ABSTRACTObjectives: We conducted a county-wide survey to assess the ability and willingness of health care workers to report to work during a pandemic influenza and a severe earthquake and to identify barriers and strategies that would help them report to work.Methods: A stratified random sample of 9211 health care workers was selected from the Washington state licensure database and from health care agencies. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 21 publications
(44 reference statements)
3
65
0
3
Order By: Relevance
“…This is further supported by recent research that has shown a health cohort to have lower perceived levels of importance in emergency response in a severe earthquake compared to a pandemic. 21 However, the threat component of the EPPM may also be an important contributor to willingness to respond and should not be ignored in future programmatic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by recent research that has shown a health cohort to have lower perceived levels of importance in emergency response in a severe earthquake compared to a pandemic. 21 However, the threat component of the EPPM may also be an important contributor to willingness to respond and should not be ignored in future programmatic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…3,18 Pharmacists can be relied on to participate in an emergency response; in one study that surveyed healthcare workers, researchers found that 93% of pharmacists would be willing to report to work during a future pandemic. 19 The participation of pharmacists in public health responses is particularly important given their specialized skillset and knowledge.…”
Section: Practice Of Pharmacymentioning
confidence: 99%
“…12 Among health care workers from varied sectors (eg, hospitals and home health care agencies) in Washington State (USA), 11% indicated that they would not report to work during an influenza pandemic. 13 While EMS workers are generally more willing to respond during an influenza pandemic than other responder cohorts, gaps in willingness remain. A survey of Australian prehospital emergency medical workers found that 89% were very anxious about working during an influenza pandemic.…”
Section: Introductionmentioning
confidence: 99%